Assembly of carbon nanotubes into microparticles with tunable morphologies using droplets in a non-equilibrium state. Issue 29 (23rd March 2017) - Tomii, Sakurako; Yamada, Masumi; Mizuno, Masahiro; Yamada, Yasuhiro; Kojima, Takashi; Kushida, Masahito; Seki, Minoru
Abstract : A microfluidic process to assemble carbon nanotubes (CNTs) into micrometer-sized particles is presented, using aqueous droplets in a non-equilibrium state. Abstract : Carbon nanomaterials assembled into micrometer-scale configurations are highly useful because of their unique molecular transport and adsorption properties, improved operability, and versatility in industrial/research applications. Here we propose a facile approach to assemble carbon nanotubes (CNTs) into monodisperse microparticles through rapid condensation and accumulation of CNTs in aqueous droplets in a non-equilibrium state. The droplets were generated by means of a microfluidic process or membrane emulsification, using a water-soluble polar organic solvent as the continuous phase. Because water molecules in the droplets were rapidly dissolved into the continuous phase, the CNTs were dramatically condensed and stable microparticles were finally formed. We prepared microparticles using both multi-walled and single-walled CNTs, and the size was controllable in the range of 10–40 μm simply by changing the initial CNT concentration. Interestingly, the morphologies of the particles were not spherical in many cases, and they were controllable by changing the type of the organic solvent and/or using additives in the dispersed phase. Physicochemical characterization suggested good compatibility of the CNT microparticles when used as supports for catalysts, adsorbents, and electrodes.